Climate Effects on Prey Vulnerability Modify Expectations of Predator Responses to Short- and Long-Term Climate Fluctuations - Morin, Aïssa; Chamaillé-Jammes, Simon; Valeix, Marion (Frontiers in Ecology and Evolution, 2021)
Climate changes affect the distribution and abundance of organisms, often via changes in species interactions. Most animals experience predation, and a number of models have investigated how climate fluctuations can influence predator-prey dynamics by affecting prey abundance through changes in resource availability. However, field studies have shown that prey vulnerability is a key feature determining the outcome of predator-prey interactions, which also varies with climatic conditions, via changes in prey body condition or in habitat characteristics (e.g. vegetation cover). In this theoretical work, we explore, with large mammals of African savannas in mind, how the interplay between climate-induced changes in prey abundance and climate-induced changes in prey vulnerability affects the immediate and long-term responses of predator populations. We account for prey body condition and habitat effects on prey vulnerability to predation. We show that predictions on how predator abundance responds to climate fluctuations differ depending on how climate influences prey vulnerability (habitat characteristics vs. prey body condition). We discuss how species traits influence the relative importance of the different sources of vulnerability. For example, our results suggest that populations of cursorial predators (such as spotted hyaenas) are expected to fare better than populations of ambush predators (such as African lions) in African ecosystems that will be characterized by an aridification. This study highlights the importance of understanding, and accounting for, the vulnerability factors associated to a given predator-prey pair, and improves our comprehension of predator-prey relationships in a changing climate.